Addiction Problems of Young People and Ways to Solve Them - Normurodova Iroda Orol qizi (Genius Journals, 2023)
In the article, the author commented on one of the current issues of youth, addiction problems and ways to solve them. In the process of upbringing, spiritual and educational issues are always in the forefront and the indifference of parents in the family was discussed. He made suggestions about preserving respect for national traditions
Keywords: addiction; Internet; education; environment